Implementasi Metode Fami Bisyauqin Terhadap Peningkatan Kualitas Hafalan Santri Bilghoibi (Kuliah) Di PPTQ Al-Muqorrobin Ponorogo - Dewi Salmah (CV Omah Kreator, 2025)
A Memorizing the Al-Qur'an requires a long time to complete and various methods are used to maintain the quality of memorization. The influence of the fami bisyauqin method on the quality of memorizing the Al-Qur'an is the focus of this research. The fami bisyauqin method is a new breakthrough for the PPTQ Al-Muqorrobin Ponorogo Institute after using the muroja'ah binafsi method for a long time. This idea received a positive response and full support from the students, to foster a muroja'ah spirit in the midst of worldly activities. This research aims to explain the implementation of the fami bisyauqin method at PPTQ Al-Muqorrobin Ponorogo, as well as the influence of the fami bisyauqin method on the quality of memorizing the Al-Qur'an at PPTQ Al-Muqorrobin Ponorogo. This type of research is field research using descriptive qualitative methods, namely research that describes or explains the object being studied based on natural or real conditions (without experimental situations) to create a systematic general picture in detail, factual and accurate. The research results describe that 1) the fami bisyauqin method is one of the most effective methods for improving the quality of memorizing the Al-Qur'an. This method helps students become accustomed to and trained in reading the Koran. Unconsciously, the brain will record the reading that is read so that the quality of students' memorization will be well maintained. 2) Supporting activities in the implementation of the fami bisyauqin such as muroqobah, simaan jum'at legi, and riyadhah. 3) Supporting and inhibiting factors in implementing the fami bisyauqin method are health, interest, motivation, infrastructure and social environment